[Rezension von: Ebel, Jonathan H., 1970-, From dust they came : government camps and the religion of reform in New Deal California] - Remillard, Arthur (A journal of church and state, 2025)
In much of his previous work, Jonathan Ebel has distinguished himself as a scholar of religion and war, focusing on how ordinary people outside conventiona